2022
DOI: 10.31091/mudra.v37i3.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dragon Ornaments in The Contexts of Batik Cloth, and The Cultures of Javanese and Tionghoa in Indonesia

Abstract: This paper was created to discuss an interesting issue, dragon ornament in batik cloth, the value of its aesthetics, and its context to Javanese and Tionghoa (Chinese) culture in Indonesia. This paper attempts to answer several questions including what is a dragon ornament, why is a dragon ornament applied to batik cloth, how is it aesthetic, and how is the relationship between Javanese and Tionghoa dragon ornaments in Indonesia. This issue is approached using interpretation perspective, both specifically in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…If the statement is a fact, then Brandy Melville should restrict it's employees and set rules for them to be respectful to their customers instead of being rude. Because these not managed employees will have bad impact on the brand image, and some competitors of Brandy Melville may take the chance to make Brandy Melville caught up in public opinion [9,10]. Therefore, Brandy Melville should pay more attention to its staff management problems, since this action would attract more customers for Brandy Melville, and the negative judgments of Brandy Melville will also be disappeared.…”
Section: Suggestionsmentioning
confidence: 99%
“…If the statement is a fact, then Brandy Melville should restrict it's employees and set rules for them to be respectful to their customers instead of being rude. Because these not managed employees will have bad impact on the brand image, and some competitors of Brandy Melville may take the chance to make Brandy Melville caught up in public opinion [9,10]. Therefore, Brandy Melville should pay more attention to its staff management problems, since this action would attract more customers for Brandy Melville, and the negative judgments of Brandy Melville will also be disappeared.…”
Section: Suggestionsmentioning
confidence: 99%
“…For example, the dulohupa ornament is a symbol of deliberation and decision-making consensus, and the huyula ornament is a symbol of cooperation in building the country (Dulo Ito Momongu Lipu). This means, ornaments as cultural products not only display visual beauty, but also contain symbolic values related to local cultural wisdom (Widayat, 2022). The emergence of symbolic motifs sourced from the local wisdom of Gorontalo communities added to the diversity of traditional motifs and the value of karawo textiles (Hasdiana et al, 2019).…”
Section: Karawo Textile Development: 2000-2010mentioning
confidence: 99%
“…This ornament is often applied to batik cloth because it has a symbolic meaning as a protector and symbol of power, identical to the king. Such as finding research about dragon ornaments in batik cloth shows that Javanese dragons can be found in Yogyakarta and Surakarta (Widayat, 2022).…”
Section: Introductionmentioning
confidence: 99%